Libyan Foreign Policy Towards Africa in Light of Regional and International Changes: An Analytical Study (Al-Farooq Journal of Sciences, 2026)
This study examined Libyan foreign policy toward Africa in light of regional and international changes. It analyzed the main determinants shaping this orientation and explored the impact of regional and international transformations on the effectiveness of Libya’s role within the African continent. The study adopted the descriptive analytical approach, while also benefiting from the historical approach to understand the development of Libyan-African relations. The study concluded that Africa represents a strategic sphere in Libyan foreign policy due to Libya’s geographical location and its connection to issues of security, migration, borders, and the Sahel-Saharan region. It also showed that the transformations Libya experienced after 2011 weakened its role in Africa because of political division and institutional fragility. The study emphasized the need to develop a clear African strategy based on unifying foreign policy decision-making, activating Libyan diplomacy, and strengthening cooperation with the African Union and neighboring African states.
Keywords: Libyan foreign policy, Africa, regional changes, international changes, African Union.